Aspek-aspek Linguistik dalam Proverba Bahasa Inggris - Azhar, Iqbal Nurul (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2014)
This qualitative research is an attempt to explain the structural, lexical, and semantic aspects of English proverbs by using a grounded theory approach. The design of this research is an embedded single case study which employs Spradley’s qualitative data analysis techniques. This study used a non-participant observation method which involved scanning, reading, and taking-note techniques. The data were then categorized into taxonomies by using distributional and identity method. The result of the research shows that: (1) the structures of English proverbs are varied in forms, from the simple to complex, (2) the inter-constituent relations are not rigid, (3) some unique lexical formulas construct the proverbial structures, and (4) lexicons that construct English proverbs have their own semantic distinctive functions.